THE INFLUENCE OF INNOVATION ON CLASS MANAGEMENT COMPETENCE WITH THE APPLICATION OF THE PROMBLEM BASED LEARNING (PBL) MODEL - Nur Wahyuni; Dinda Widyastika; Rudi Hermansyah Sitorus; Arnisa Rambe (Jurnal Scientia, 2023)
This study aims to analyze the effect of the application of problem based learning (PBL) and classroom management innovations on improving the quality of learning and critical thinking skills of students in elementary schools. The research methodology is a meta-analysis that collects information from relevant articles that meet the research criteria. The data were then analyzed and checked for generalizable results. The results showed that the application of Problem Based Learning (PBL) methods and innovations in classroom management had a positive effect on the quality of learning and students' critical thinking. Based on the results of this study it can be concluded that the application of problem-based learning methods (PBL) and classroom management innovations are important for improving the quality of elementary school learning.